2013
DOI: 10.1093/mnras/stt951
|View full text |Cite
|
Sign up to set email alerts
|

Main-belt comets in the Palomar Transient Factory survey – I. The search for extendedness

Abstract: Cometary activity in main-belt asteroids probes the ice content of these objects and provides clues to the history of volatiles in the inner solar system. We search the Palomar Transient Factory (PTF) survey to derive upper limits on the population size of active main-belt comets (MBCs). From data collected March 2009 through July 2012, we extracted ∼2 million observations of ∼220 thousand known main-belt objects (40% of the known population, down to ∼1-km diameter) and discovered 626 new objects in multi-nigh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 69 publications
2
46
0
Order By: Relevance
“…It reinforces the idea that rotational instability is one of the important fates that comets may suffer, especially for those sub-kilometre sized. In addition to sky surveys such as Pan-STARRS, there have been attempts to search for MBCs with targeted observations of known asteroids in main-belt orbits to search for activity (Hsieh 2009), and in archival data from the Canada-France-Hawaii Telescope Wiegert 2009, 2010;Sonnett et al 2011) and the Palomar Transient Factory (Waszczak et al 2013). Recently, a citizen science project 2 to crowd source the visual identification of MBCs has been employed in the search (Hsieh et al 2016;Schwamb et al 2017).…”
Section: Discovery Of Mbcsmentioning
confidence: 99%
“…It reinforces the idea that rotational instability is one of the important fates that comets may suffer, especially for those sub-kilometre sized. In addition to sky surveys such as Pan-STARRS, there have been attempts to search for MBCs with targeted observations of known asteroids in main-belt orbits to search for activity (Hsieh 2009), and in archival data from the Canada-France-Hawaii Telescope Wiegert 2009, 2010;Sonnett et al 2011) and the Palomar Transient Factory (Waszczak et al 2013). Recently, a citizen science project 2 to crowd source the visual identification of MBCs has been employed in the search (Hsieh et al 2016;Schwamb et al 2017).…”
Section: Discovery Of Mbcsmentioning
confidence: 99%
“…We observed Chiron on 2010 May 22 from the Palomar Transient Factory's 48 inch telescope (PTF; cf. Law et al 2009;Waszczak et al 2013;Ofek et al 2012aOfek et al , 2012b and found an R-band magnitude (m R ) = 17.86 ± 0.03. For a bare nucleus of ∼200 km diameter with ∼15% reflectance (Fernández et al 2002) and an IAU phase curve slope parameter of G = 0.15 (cf.…”
Section: Chiron and The Active Centaursmentioning
confidence: 99%
“…On the other hand, untargeted searches, such as that conducted by the PANSTARRS1 and Palomar Transient Factory surveys (Hsieh et al 2015a;Waszczak et al 2013), introduce fewer selection biases than targeted surveys, and if conducted as part of larger multi-use surveys, can be much more efficient in terms of required observing effort. The lack of strong selection biases in untargeted surveys also means that more meaningful estimates of the total size of the MBC population can be made than would be possible from a targeted survey.…”
Section: Mbc Search Effortsmentioning
confidence: 99%
“…Discovery rates of untargeted search will inevitably be lower than those of targeted surveys though, meaning that more objects must be surveyed to achieve each successful new discovery. Reliable automated techniques must also be developed to search large data sets for comet candidates (e.g., Hsieh et al 2012b;Waszczak et al 2013), given that they will generally be too large to analyze manually. Citizen science initiatives, where internet-based tools are used to solicit and gather large numbers of image classifications from members of the general public (e.g., Lintott et al 2008) and which exploit the pattern recognition abilities of the human eye that can be difficult to replicate with automated algorithms, may also prove to be useful for analyses of these large data sets.…”
Section: Mbc Search Effortsmentioning
confidence: 99%